Flexural Performance of Cross-Laminated Bamboo (CLB) Slabs and CFRP Grid Composite CLB Slabs. (3rd November 2019) - Lv, Qingfang; Wang, Weiyang; Liu, Ye
Abstract : In order to accord well with the requirements of sustainable development and green construction, a cross-laminated bamboo composed of an odd number of orthogonally oriented layers of bamboo scrimber is proposed in this paper. Adjacent bamboo layers are face-bonded by structural adhesives under pressure. The uniform mechanical and physical properties can be obtained through the orthogonal layup. Flexural performances of three groups of one-way CLB slabs and two groups of one-way CLB slabs strengthened with CFRP grids were investigated via four-point monotonic loading configuration until failure. Experimental parameters of thickness of the layer, number of layers, and manufacturing processes of CFRP grids were taken into consideration. Experimental observations showed that the failure of the CLB slab was brittle, and different failure modes were found in the CLB slab with CFRP grids via different manufacturing processes. Test results showed that the load-carrying capacity increased with the thickness of the layer, number of layers, and application of CFRP grids pressed in the bamboo layer, but the CFRP grids pressed in the interface of adjacent bamboo layers weakened the load-carrying capacity. The strain analysis demonstrated that the compression region was utilized with more efficiency via CFRP grids pressed in the bamboo layer, and the plane cross section assumption is suitable for both CLB slab and CLB slab strengthened with CFRP grids. A theoretical calculation method of flexural load-carrying capacity was proposed for the CLB slab, the accuracy of which was proved.